2005
DOI: 10.1098/rstb.2004.1608
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding the molecular basis of bacterial DNA segregation

Abstract: Bacteria ensure the fidelity of genetic inheritance by the coordinated control of chromosome segregation and cell division. Here, we review the molecules and mechanisms that govern the correct subcellular positioning and rapid separation of newly replicated chromosomes and plasmids towards the cell poles and, significantly, the emergence of mitotic-like machineries capable of segregating plasmid DNA. We further describe surprising similarities between proteins involved in DNA partitioning (ParA/ParB) and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 134 publications
2
94
1
Order By: Relevance
“…Treadmilling models are based upon the two ends of a filament being different, where one end is growing and the other depolymerizing. Such treadmilling of ParA2 could move the DNA to which the ParA2 filament is bound only if ParA2 were also bound to a fixed host factor (43). However, the bipolar nature of the ParA2-DNA filament that we observed suggests that such models are unlikely, or that any polarity must be conferred by one end of the filament being in contact with ParB2 or some other as yet undetermined element.…”
Section: Discussioncontrasting
confidence: 38%
“…Treadmilling models are based upon the two ends of a filament being different, where one end is growing and the other depolymerizing. Such treadmilling of ParA2 could move the DNA to which the ParA2 filament is bound only if ParA2 were also bound to a fixed host factor (43). However, the bipolar nature of the ParA2-DNA filament that we observed suggests that such models are unlikely, or that any polarity must be conferred by one end of the filament being in contact with ParB2 or some other as yet undetermined element.…”
Section: Discussioncontrasting
confidence: 38%
“…The structure of the proU::tet lesion was confirmed by PCR and DNA sequencing (GATC Biotech) and then used as a template for the insertion of the modified icsB-proU-gfp-cat promoters using primer set icsB.fw. 40 ␤-Galactosidase assay. The transcription of the mxiC::lacZ fusion was measured in cultures of the wild type and hns and virB mutant strains grown overnight in LO or LB broth at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…ParB-like proteins bind to a cis-acting DNA sequence called parS (5,28,35,40,67,70), and it has been found that the VirB binding site at the icsB promoter retains the features of a parS sequence (73,76). Normally, such parS elements are located adjacent to the genes coding for the ParA and ParB proteins (35).…”
mentioning
confidence: 99%
“…Bacterial cells also contain the ParA family of ATPases that comprise a cytoskeletal element (Gerdes et al 2004;Leonard et al 2005;Hayes and Barilla 2006). ParA proteins are required for plasmid and chromosomal DNA segregation in many bacteria and have recently been shown to assemble polymers both in vivo and in vitro (Barilla et al 2005;Lim et al 2005;Adachi et al 2006;Ebersbach et al 2006;Fogel and Waldor 2006;Bouet et al 2007).…”
mentioning
confidence: 99%